2002
DOI: 10.1016/s0304-3878(02)00002-0
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate regimes, inflation and output volatility in developing countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 9 publications
(6 reference statements)
2
52
0
3
Order By: Relevance
“…On the other hand Tornell and Velasco (2000) show that …xed rates can induce …scal laxity, and this may increase volatility. Bleaney and Fielding (2002) present a model in which tighter exchange rate pegs reduce in ‡ation volatility except in the case of the multi-lateral pegs maintained by the Francophone countries in Africa, which increase volatility because the peg prevents monetary authorities from o¤setting the e¤ects of external shocks.…”
Section: The Role Of the Exchange Rate Regimementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand Tornell and Velasco (2000) show that …xed rates can induce …scal laxity, and this may increase volatility. Bleaney and Fielding (2002) present a model in which tighter exchange rate pegs reduce in ‡ation volatility except in the case of the multi-lateral pegs maintained by the Francophone countries in Africa, which increase volatility because the peg prevents monetary authorities from o¤setting the e¤ects of external shocks.…”
Section: The Role Of the Exchange Rate Regimementioning
confidence: 99%
“…30 In column 1 of Table 4 we add the exchange rate regime indicator (XRAT E) to our baseline regression and in column 2 we add the square of the exchange rate regime in order to test for non-linearities of the sort discussed by Bleaney and Fielding (2002). The additional control does not alter the role of openness and is statistically insigni…cant.…”
Section: The Role Of the Exchange Rate Regimementioning
confidence: 99%
See 1 more Smart Citation
“…Among others, this is documented by Bleaney and Fielding (2002) for the CFA franc countries. The updated descriptive statistics for the post-1999 period displayed in section 2 confirm that, in fact, the African countries that have been pegged to the euro display a better inflation performance than the rest of the continent.…”
Section: Empirical Strategymentioning
confidence: 85%
“…For the period of the peg to the French franc, Bleaney and Fielding (2002) found that the exchange rate regime helped the CFA countries to achieve significantly lower levels of inflation than the typical floating-rate developing country (although at the cost of higher macroeconomic volatility). As Table 1 shows, such conclusion seems to hold also for the period of the peg to the euro.…”
Section: Inflationmentioning
confidence: 99%